1999
DOI: 10.1016/s0002-9440(10)65199-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Excitotoxicity in Transgenic Mice Overexpressing Neuronal Cyclooxygenase-2

Abstract: In this study we describe the generation of a transgenic mouse model with neuronal overexpression of the human cyclooxygenase-2 , h(COX)-2 , to explore its role in excitotoxicity. We report that overexpression of neuronal hCOX-2 potentiates the intensity and lethality of kainic acid excitotoxicity in coincidence with potentiation of expression of the immediate early genes c-fos and zif-268. In vitro studies extended the in vivo findings and revealed that glutamate excitotoxicity is potentiated in primary corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(142 citation statements)
references
References 50 publications
7
133
0
2
Order By: Relevance
“…Conversely, PTGS inhibition by genetic or pharmacological means after neuronal damage has been initiated results in neuroprotection [9,15,18,21,26,63]. While this dichotomy is well defined for the studies mentioned above, it has also been demonstrated that mice over expressing a human form of PTGS-2 solely in neurons, had increased KA induced mortality [27]. These results described by Kelley et al are difficult to reconcile with the observation described in our study since the only endpoint measured in their study was mortality as opposed to ours which measured seizure intensity and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PTGS inhibition by genetic or pharmacological means after neuronal damage has been initiated results in neuroprotection [9,15,18,21,26,63]. While this dichotomy is well defined for the studies mentioned above, it has also been demonstrated that mice over expressing a human form of PTGS-2 solely in neurons, had increased KA induced mortality [27]. These results described by Kelley et al are difficult to reconcile with the observation described in our study since the only endpoint measured in their study was mortality as opposed to ours which measured seizure intensity and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent investigations have found a potentiation of excitotoxicity in transgenic mice overexpressing neuronal COX-2 [37] and a significant reduction in ischemic brain injury in COX-2-deficient mice [36,62]. COX-2 expression by itself does not lead to neuronal death since a variety of healthy neuronal populations throughout the CNS express COX-2 mRNA and protein under normal conditions [5,77] and COX-2 expression can be experimentally induced without causing neuronal death [56].…”
Section: Discussionmentioning
confidence: 99%
“…An increased availability of unesterified AA and some of its eicosanoid products could promote neuronal excitability, glutamatergic neurotransmission, and seizure propagation (Bazán, 1989;Kelley et al, 1999;Kolko et al, 1996;Kunz and Oliw, 2001;Li et al, 1997;Lysz et al, 1987;Strauss and Marini, 2002;Wallenstein and Mauss, 1984). In contrast to its effect on PLA 2 signaling via AA, LiCl feeding is reported to reduce brain phospholipase C activation by cholinomimetics (Casebolt and Jope, 1989;Ormandy et al, 1991;Song and Jope, 1992).…”
Section: Discussionmentioning
confidence: 99%